Repercussões econômicas das contratações do FNE no setor agroindustrial do nordeste, sob a ótica da matriz de insumo-produto do nordeste (1989-2008) - Silva, Raul Klebersom Moura da (2010)
Evaluates the economical repercussion of FNE financing cotracts in the agroindustry sector during the period of 1989 to 2008, innovating, in relation to traditional assays, as it changes the focus analysis of the Program's sphere to the scope of the characteristically activities of the sector. For doing só, it has been used as a tool for impact measurement, the recently up-t0-date Northeast Input-output Matrix> Under this way, measuring the individual impacts of the activities and, afterward, aggregating them, there has been found the results for the Sactor. Overall, the mentioned results confirmed that the FNE resources directed to the agribusiness sector have been fundamental to the northeastern economy, considering that, representing only 6,9% of the total applied by the mentioned Fund in the Region, it has impacted on the Gross Value insertion of R$ 11,7 billions in the production: which, for its turn, has been materialized in increments on the Region's PIB of about R$ 5,9 billions and in the creation and maintenance in an average of 15.145 work opportunities each year, during the analysis period. FNE has still been responsible for impacts of R$ 1,7 billion on the total wages and for the generation of around R$ 1,9 billion in tributary income in favor of the Public Administratin. Regarding this, the sectors that manufacture sugar, and cellulose and mechanical paste have been the ones that presented the biggest impacts and the best multipliers in practically all the variables, studied. In despite of the mentined results, the elevated percentages of overflowing and low pure bonding indexes identified have evidenced the Northeast as a products buyer with a bigger aggregated value in relation to those to whom it sells, which is what turns it into an exporter of wealth and taxes, as well as an in deficit in relation to its trade balance and meaningful dependent on the productive sectors of rest of the country.